Новый рассвет: роман / С. Браун ; пер. с англ. Н. Сапрыкиной, Е. Токаревой - Браун С. (Наслаждение, 1997)
Экземпляры: (20180816) / Инвентарный номер: 32914 / Цена: 14.50 / Авт.знак: Б 87 / ББК: 84(7Сое)